การสกัดด้วยเอนไซม์และสมบัติเชิงหน้าที่ของใยอาหารจากพุทราพันธุ์สามรส Ziziphus mauritiana Lam. - ชมัยพร แรงกลาง (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objectives of this research were to study the extract condition of mucilage and the production of jujube (Ziziphus mauritiana Lam.) dietary fiber powder from jujube pomace using enzyme processing, and also to study the functional properties of mucilage powder and jujube dietary fiber powder. The extract condition which provided the highest mucilage yield was incubated jujube pulps for 9 days, blanching at 85ºC for 3 min, mixing jujube pulp with water in the ratio of 1:7 at 600C, and precipitating the mucilage solution with ethanol in the ratio of 1:3. From the study of functional properties of mucilage powder compared with guar gum and xanthan gum, results showed that mucilage powder had the L* value similar to xanthan gum but higher than guar gum. Water holding capacity was 11.77 g water/ g dry weight. The value of oil absorption was higher than guar gum and xanthan gum, respectively (p<0.05). The emulsion capacity was less than xanthan gum and guar gum, respectively (p<0.05). The rheological properties were found that mucilage solution exhibited pseudoplastic behavior as the same with guar gum. This research also indicated that the higher concentration of mucilage solution and pH could increase the viscosity. However, when increasing temperature the viscosity was decreased. From the production of jujube dietary fiber powder using enzyme processing, results indicated that the optimum washing condition of jujube pomace was washing jujube pomace with water in the ratio of 1:2 for 3 times. Then treated jujube pomace with Pectinex® Ultra SP-L by varying the enzyme concentration (0-3.0% v/w) and hydrolysis time (0-6 h), results showed that the reducing sugars were increased when increasing concentration and hydrolysis time. The optimum process condition was treated jujube pomace with enzyme concentration of 2.0%(v/w) and hydrolyzed for 0, 0.5, 1, 2, and 4 h. This condition can be hydrolyzed jujube pomace in 5 levels different in the amount of reducing sugars (1.01, 17.79, 19.29, 22.61 and 23.98 mg glucose/ g fresh weight). The effect of these treatment conditions on jujube pomace showed that jujube pomace at hydrolysis time for 4 h had significantly higher soluble dietary fiber content than other hydrolysis times (p<0.05). Then studying the rate of hydrolysis by using enzyme concentration of 2.0% (v/w) at 4 h hydrolysis time, it was found that the reducing sugars increased and stable at hydrolysis time for 6 h. From this research, it can be divided the jujube dietary fiber powder into 3 levels according to the different of glycosidic bonds cleavage which were jujube dietary fiber powder from treated jujube pomace with enzyme for 0, 4, and 6 h, respectively. The jujube dietary powder at 6 h hydrolysis time had significantly higher soluble dietary fiber content than other hydrolysis times (p<0.05). From the studying of functional properties of jujube dietary fiber powder found that jujube dietary fiber powder at 6 h hydrolysis time had water holding capacity, oil holding capacity and emulsion capacity significantly higher than other hydrolysis times (p<0.05). Sensory evaluation of jujube dietary fiber powder at 6 h hydrolysis time showed that this condition had significantly greater scoring in color, jujube fruit odor, fine powder, spread and suspension ability than other hydrolysis times.